Prevalence of Tick-Borne Pathogens in Host-Seeking Amblyomma americanum (Acari: Ixodidae) and Odocoileus virginianus (Artiodactyla: Cervidae) in Florida. Issue 4 (26th April 2016) - Sayler, Katherine A.; Loftis, Amanda D.; Beatty, Sarah K.; Boyce, Carisa L.; Garrison, Elina; Clemons, Bambi; Cunningham, Mark; Alleman, Arthur R.; Barbet, Anthony F.
Abstract: Amblyomma americanum (L.), the lone star tick, is an aggressive tick that is expanding its geographic range within the United States. This tick is the vector for the human and veterinary pathogens Ehrlichia chaffeensis and Ehrlichia ewingii and is associated with other microbes of unspecified pathogenicity including Rickettsia amblyommii, Panola Mountain Ehrlichia, and Borrelia lonestari . In Florida, there has been sparse contemporary data on the prevalence of these organisms in host-seeking lone star ticks. To determine the prevalence of this tick and associated microbes in North Central Florida state parks, ∼1, 500 lone star tick specimens were collected between 2010 and 2012 analyzed by polymerase chain reaction (PCR) sequencing. Additionally, 393 white-tailed deer, Odocoileus virginianus (Zimmerman), samples were analyzed for pathogen prevalence using molecular methods and serology. In lone star ticks, 14.6, 15.6, and 57.1% were positive for E. chaffeensis, E. ewingii, and Rickettsia spp. DNA, respectively. Panola Mountain Ehrlichia or B. lonestari DNA were each detected in nearly 2% of tick specimens. In white-tailed deer, 7.3% were PCR positive for E. chaffeensis, 6.0% for E. ewingii, and 3.2% for rickettsial species . Approximately 45% of white-tailed deer specimens had antibodies to Ehrlichia spp., and <1% had antibodies to Borrelia burgdorferi . In summary, E. chaffeensis, E. ewingii, and spotted fever group rickettsia are highly prevalent in host-seeking lone star ticks and in white-tailed deer in Florida. The molecular and serological evidence of these microbes underscore their zoonotic potential in this region.